Value of Other Endovascular Techniques Among Patients with MERCI Device Failure during the Treatment of Acute Ischemic Stroke - Hassan, Ameer E (Zeenat Qureshi Stroke Research Center, 2013)
BACKGROUND: The MERCI Retrieval system (Concentric Medical, Mountain View, CA) was the first FDA-approved device for mechanical thrombectomy in patients with acute ischemic stroke. It remains one of the most commonly used devices today despite its failure to restore blood flow in approximately 50% of the occlusions after technically successful deployment and retrieval. It remains unclear whether additional endovascular techniques or continued use of MERCI device can achieve recanalization post-MERCI failure. OBJECTIVE: To analyze the outcome of continued MERCI retriever use compared with other endovascular techniques after initial failure. METHODS: Failure of MERCI retriever was defined by successful deployment and retrieval of MERCI across target occlusion without recanalization in a single pass. Pre- and post-treatment cerebral angiogram was classified using the Qureshi Grading Scale (QGS). Recanalization was defined by a reduction in ≥ 1 QGS grade between pre- and post-treatment cerebral angiogram in the Qureshi Grading Scale (QGS).We ascertained and compared the angiographic and clinical results with continued use of MERCI retriever or other endovascular techniques in patients following MERCI failure. RESULTS: A total of 40 patients (53% men) had MERCI retrieval in this cohort with a mean age (±standard deviation) of 66.8 years ± 16 years and a mean admission National Institutes of Health Stroke Scale (NIHSS) score of 16.8 ± 6.7. Of the 40 patients treated with MERCI retrieval, there were 26 patients with MERCI failure. In group 1, there were 11 patients who underwent continued MERCI use and group 2 consisted of 15 patients who underwent an alternate endovascular technique. There was no significant difference in age, risk factors, or outcomes between the groups. The rate of recanalization (82% versus 80%, p = 1.0), asymptomatic intra cerebral hemorrhage (18% versus 13%, p = 0.77) and favorable outcome at discharge (27% versus 20%, p = 0.66) were similar amongst the two groups. CONCLUSIONS: Continued attempts using the MERCI device did not result in higher recanalization rates when compared to alternate endovascular treatment modalities following initial MERCI failure. Both techniques produced comparable rates of recanalization and favorable outcome.